2022
DOI: 10.1186/s12884-022-04712-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of 2860 cases of diabetes in pregnancy: a single-center retrospective study

Abstract: Background To investigate the epidemiological, clinical characteristics and outcomes of diabetes in pregnancy (DIP). Methods This single-center, retrospective study included 16,974 pregnant women hospitalized during 2018–2019. Among them, 2860 DIP patients were grouped according to diabetes type, glycemic status, and insulin use. Multivariate logistic regression analysis was conducted. Results The inci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…But, if only women with risk factors for GDM are screened, the proportion of missed diagnosis will be very high leading to extraordinary complication rate. 23,24 Our study documented a strong relationship of increased AFI and LGA fetuses with GDM. Considering easy accessibility, frequent and common use of ultrasound; we suggest (after further studies and multicenter trials) the inclusion of these ultrasound parameters as routine screening tools for detection of GDM in second half of pregnancy in undiagnosed cases.…”
Section: Discussionmentioning
confidence: 51%
“…But, if only women with risk factors for GDM are screened, the proportion of missed diagnosis will be very high leading to extraordinary complication rate. 23,24 Our study documented a strong relationship of increased AFI and LGA fetuses with GDM. Considering easy accessibility, frequent and common use of ultrasound; we suggest (after further studies and multicenter trials) the inclusion of these ultrasound parameters as routine screening tools for detection of GDM in second half of pregnancy in undiagnosed cases.…”
Section: Discussionmentioning
confidence: 51%
“…Abnormal lipid metabolism in patients with hypertension can easily be complicated by abnormal glucose metabolism. Previous studies have shown that gestational diabetes may be related to puerperal infection and Cesarean section incision infection ( 16 18 ). However, this study showed that the incidence of puerperal infection and Cesarean section infection in pregnant women with GDM was not different from that in the non-GDM group.…”
Section: Discussionmentioning
confidence: 99%